(6x+4)-(-6x+5)=

Simple and best practice solution for (6x+4)-(-6x+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+4)-(-6x+5)= equation:


Simplifying
(6x + 4) + -1(-6x + 5) = 0

Reorder the terms:
(4 + 6x) + -1(-6x + 5) = 0

Remove parenthesis around (4 + 6x)
4 + 6x + -1(-6x + 5) = 0

Reorder the terms:
4 + 6x + -1(5 + -6x) = 0
4 + 6x + (5 * -1 + -6x * -1) = 0
4 + 6x + (-5 + 6x) = 0

Reorder the terms:
4 + -5 + 6x + 6x = 0

Combine like terms: 4 + -5 = -1
-1 + 6x + 6x = 0

Combine like terms: 6x + 6x = 12x
-1 + 12x = 0

Solving
-1 + 12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 12x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 12x = 0 + 1
12x = 0 + 1

Combine like terms: 0 + 1 = 1
12x = 1

Divide each side by '12'.
x = 0.08333333333

Simplifying
x = 0.08333333333

See similar equations:

| Y(5-2)=52 | | (x+12)*4=90-2x | | 4x^4-2x^3+7x^2+3x+9=0 | | 2r-.75=1 | | (2x+1)+(-1x+9)= | | 4(x+12)=90-2x | | 4(4+12)=90-2x | | 22=6p+4 | | a-4x=14 | | 5x-2(-2x+1)=2(2x+15) | | 10x^2-135=25 | | -6(x+1)-12=28+8 | | 22=6p+4p | | 4(-5)+2=x+3 | | 44-3x=9-8x | | 3(-2x-7)=3(-9x+5) | | 64-5x=31x+24 | | 0.3333(2x-5)=3 | | (4x-12)=(2y+16) | | 16+5z=-4 | | 4+65x=39x+10 | | 11+-3= | | 4x+6=-50-4x | | 9+3(x+2)=21 | | a*5+71=a*9-5 | | 2(q+3)=1 | | 8y-2=-8 | | -22+7= | | 0.625x+0.75=7 | | 8+-7= | | 3(x+1)+7(x+3)=64 | | 23-(7)= |

Equations solver categories